Breast Cancer Patient Characeristics By Menarche In Adam Malik Hospital 2014-2017 - Ervina, Cynthia; hermansyah, dedy (Talenta Publisher, 2020)
Background. Breast cancer is one of the most diagnosed cancer in the world. Breast cancer starts when the breast cell grows abnormally and turns malignant. In Indonesia, breast cancer is the most diagnosed cancer in women. Up to now, the cause of breast cancer has not been identified yet. There are many factors that increase the risk of breast cancer, one of them is the early age of menarche. Objective. This study aims to obtain characteristics of breast cancer patients based on age of menarche in RSUP Haji Adam Malik in 2014-2017. Method. The study was designed in observational with descriptive method. The sampling had been done using total sampling technique. Results. Based on general characteristics, the majority of breast cancer patients are in the range of 40-49 years old (38,5%), graduated high school (45,2%), unemployed (66,3%), and do not have family history (94,2%). Majority of patients have stadium IIIB breast cancer (41,3%). The most diagnosed histopathology is Invasive Ductal Carcinoma (78,8%). Majority of breast cancer patients have negative estrogen receptor (67,3%), negative progesterone receptor (67,3%), negative her2 (66,3%) and positive ki-67 (67,3%). Fifty three breast cancer patients (51%) have early menarche. Based on the age of menarche, the patient with early menarche mostly has stage three breast cancer, but the age of menarche does not give a specific characteristic in histopathology and immunohistochemistry. Conclusion. Age of menarche gives specific characteristic in staging but not in histopathology and immunohistochemistry.